Phage control of dual species biofilms of Pseudomonas fluorescens and Staphylococcus lentus - Sillankorva, Sanna (2010)
Despite the recent enthusiasm for using bacteriophages as bacterial control agents, there are only limited studies concerning phage interaction with their respective hosts residing in mixed biofilm consortia and especially in biofilms where the host species is a minor constituent. In the present work, a study was made of mono and dual species biofilms formed by Pseudomonas fluorescens (Gram-negative) and/or Staphylococcus lentus (Gram-positive) and their fate after infection with phages. The dual species biofilms consisted predominantly of S. lentus. The exposure of these biofilms to a cocktail containing both P. fluorescens and S. lentus phages effectively killed and removed the hosts from the substratum. Additionally, this cocktail approach also controlled the hosts released from the biofilms to the planktonic phase. The ability of phages to control a host population present in minority in the mixed species biofilm was also assessed. For this objective, the biofilms were challenged only with phage øIBB-PF7A, specific for P. fluorescens and the results obtained were to some extent unpredicted. First, øIBB-PF7A readily reached the target host and caused a significant population decrease. Secondly, and surprisingly, this phage was also capable of causing partial damage to the biofilms leading to the release of the non-susceptible host (S. lentus) from the dual species biofilms to the planktonic phase. The efficiency of phage treatment of biofilms was to some extent dependent on the number of cells present and also conditioned by the infection strategy (dynamic or static) utilized in the infection of the biofilms. Nevertheless, in most circumstances phages were well capable of controlling their target hosts.